Effect of Temperature, Salinity, and pH on Nanocellulose-Improved Polymer Gel for Oilfield Water Control - Previnah Loganathan; Harjeet Kaur Sukhbir Singh; Zulhelmi Amir (Gels)
Excessive water produced in oil reservoirs reduces oil recovery and increases the cost of water treatment. Conventional water control methods use synthetic polymer gels like PAM-PEI, which are sensitive to harsh reservoir conditions. This study investigates the use of cellulose nanofibers (CNF) to enhance polymer gels for oilfield water control under various temperatures, salinities, and pH conditions. Polymer gels were prepared by combining PAM and PEI with CNF concentrations of 1–4 wt% in deionized water. Salinity effects were studied by adding NaCl (1.5–2.5 g), while pH effects were assessed under acidic (pH 2–3), neutral, and alkaline (pH 13–14) conditions. The mixtures were stirred, homogenized, and subjected to thermal treatment in a water bath oven at temperatures ranging from 70 °C to 90 °C for gel formation. Gelation time was determined by the Sydansk gel code, and gel strength was assessed through storage modulus (G′) and loss modulus (G″) from oscillatory rheometry tests. Results show that lower temperatures increase gelation time, with higher CNF concentrations needed to elongate gelation at higher temperatures. At 30,000 ppm NaCl, gelation time decreases with increasing CNF, while at 50,000 ppm NaCl, it increases. Extreme pH conditions (pH 2–3 and pH 13–14) lead to longer gelation times with decreasing CNF concentration. While high salinity and extreme pH reduce gel strength, the addition of CNF enhances it, though this effect is minimal beyond 2–3 wt%. These findings suggest that CNF can improve the performance of polymer gels under challenging reservoir conditions.